Elements of Psychocardiology in the Psychosocial Handling of Adults with Congenital Heart Disease - Callus, Edward; Quadri, Emilia; Chessa, Massimo (Frontiers in Psychology, 2010)
When it comes to the role of the clinical psychology in the cardiac settings, or psychocardiology, there is often a focus on acquired cardiac illnesses in the rehabilitation settings. However, the increase of adults with congenital heart disease due to technological advances in cardiology and cardiac surgery have created a new emergency. It is thus necessary to reflect upon the elements of psychocardiology adapting them to this new population, also when it comes to interventional hospital settings of cardiology and cardiac surgery. This perspective article is an effort in this direction.